Effect of parent rock strength and water absorption on concrete compressive strength - رضوان ولی بیگی (Iranian Society of Structrual Engineering (ISSE), 2019)
Since the volume of aggregates in concrete is the highest among the constituent materials, their strength and water absorption can have decisive impact on the concrete ultimate strength. Therefore, it is anticipated that studying the strength of the parent rock can lead to a better understanding of the behavior of concrete. With this in mind, a project was undertaken to investigate the effect of the parent rock strength on the strength of the concrete made with the aggregates of the same rock and the results are presented in this paper. This investigation involved eight different types of rocks which were uniaxially tested to estimate their compressive strengths. The amount of water absorbed by rock samples were determined in a standard manner. The results show that the strength of the parent rocks used in this study were dependant on their moisture content because it was realized that the strength of the rocks decreases, between 25 to 64 percent, with increase in their moisture content from dry to saturate state. It was also seen that an increase of about 10 times in the strength of the parent rock, tends to increase the related concrete strength by about 46 percent. The correlation coefficient (R2) of the relationship between the resistance of rocks was evaluated and concretes made of aggregates of the cliffs was between 0.42 and 0.686. The highest correlation coefficient between the resistance of saturated rock and concrete the resulted from aggregates in the same rocks were observed.